PENGARUH PERBEDAAN METODE MELT PROCESSING DAN SISTEM LARUT TERHADAP HASIL GRAFT KOPOLIMERISASI CYCLIC NATURAL RUBBER (CNR) DENGAN GLYCIDYL METHACRYLATE (GMA) - Eddiyanto, Eddiyanto; Sipahutar, Rezwan Mulya; Nurfajriani, Nurfajriani; Pulungan, Ahmad Nasir; Herlinawtati, Herlinawati (UIN AR-RANIRY, 2024)
Although natural rubber has many good qualities, its commercial uses are limited by its low chemical reactivity and low heat stability. A derivative with better stability, Cyclic Natural Rubber (CNR), has to be chemically modified to increase its usefulness and broaden its range of applications. Investigating the effects of two different methods, the melt processing and solution system on the FTIR spectra of Cyclic Natural Rubber (CNR) graft copolymerization with Glycidyl Methacrylate (GMA) was the aim of this work. Additionally, an evaluation of the effect of Dicumyl Peroxide (DCP) and Benzoyl Peroxide (BPO) initiators on grafting results was carried out. According to FTIR spectrum analysis, the carbonyl ester (C=O) peak at roughly 1721 cm⁻¹, indicating effective grafting, was more pronounced in the melt processing approach than in the solution procedure. This implied that melt processing resulted in higher grafting efficiency. The absorption bands in the C-H stretching region (2860-2921 cm⁻¹) and the C=C stretching area (1672 cm⁻¹) show that the underlying structure of CNR has not degraded. The carbonyl index values for each composition showed that BPO performed better than DCP in the melt treatment method, however DCP as an initiator in the solution system produced a higher grafting efficiency than BPO.